Answer:
(-1)(525) and (35)(-15)
Explanation:
Here, the given expression is,
(-7)(-15)(-5),
Since, (-7)(-15)(-5) = -525 ( Because, (-) × (-) × (-) = (-) )
First option,
(-7)(-75) and (-1)(525)
= 525 and -525 ( Because, (-) × (-) = (+) and (-) × (+) = (-) )
⇒(-7)(-75) ≠ (-7)(-15)(-5)
Second option,
(-1)(525) and (35)(-15)
= -525 and -525,
Thus, (-1)(525) = (35)(-15) = (-7)(-15)(-5)
Third option,
(35)(-15) and (115)(-5)
= -525 and -575
⇒ -575 ≠ (-7)(-15)(-5)
Fourth option,
(-1)(525) and (115)(-5)
= -525 and -575
(115)(-5) ≠ (-7)(-15)(-5)
Hence, (-1)(525) and (35)(-15) are equivalent to the given expression.